Biodiversity of aerobic heterotrophic bacteria from Baron beach, Gunung Kidul, Yogyakarta - AGUS IRIANTO; PANCRASIA MARIA HENDRATI (Biodiversitas Journal of Biological Diversity, 2003)
Baron beach is a specific habitat due its characteristic as a narrow beach with outlet of sub-surface rivers. This researchhad been done in order to know its microbial characteristic. Research used survey method and bacterial identification wasdone based on comparative description. The research showed that during high tide of seawater, the total bacterial countwas 1.0 to 6.0 x 107 cfu/ml on NA and 2.0 to 7.0 x 107 cfu/ml on NA+0.5% NaCl. Furthermore, during the low tide of seawater, the total bacterial count was 1.4 to 8.8 x 108 cfu/ml on NA, and 3.2 to 9.0 106 cfu/ml on NA+0,5% NaCl. This studyfound 14 genera of bacteria and dominated by Gram-negative bacteria. The result indicated seawater influenced thenumber of bacteria present in this environment.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: bacteria, aerobic-heterotrophic, Baron